(3GdeSGFd GdeQVjI aj HjGf GJaGb Cgd GdSfI Ydi Sff GdUdGI hGdRjOjIs - (3eMeO Hf ESeGYjd Hf UdGM Hf eMeO GdMSfj, GdcMdGfj Ke GdUfYGfj, CHh EHQGgje, YR GdOjf, GdeYQha cCSdGag HGdCejQ, J (B1182 (3g` s
(3ChdgG (B:s
(3bGd Gd SGFd OGeJ EaGOJg aGdeWdhH (B/(3, EaGOI ehdGfG eMeO Hf ESeGYjd fbd ePGgH GdbGFdjf ef Cgd GdHjJ HeG CKHJg ef GdSfI GdYdeGA GdCYdGe ef CaYGd OGbhGd JKHJ ai GdUdGI s
(3BNQgG (B:s
(3aGYed Hg Ef cfJ ef MRHg hGWQM Gddhe GddhGeg EfJgG GdeQGO ef GdLhGH s
(3HChdgG Jedc jYhO Edi SfI (B1176(3g`s
(3cJHJ GdYfGhjjf HGdMeQI Ch GdUaQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B38s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqda SfI (B1176s
Keywords: (3abg GdePGgH GdCNQis